SOURCES AND ART OF THE STORIES IN THE SADDI ISKANDARI EPIC - Shahlola, Safarova (Journal of Higher Education and Academic Advancement, 2024)
In the article, the chapter of praise in "Saddi Iskandari" from the "Khamsa" epics, which occupies a special place in the works of Alisher Navoi, is analyzed ideologically and artistically. During the analysis, attention is paid to the sources of the thoughts presented in the verses, that is, the Holy Qur'an, Hadith Sharif, aspects related to the teachings of Sufism. The poetic lines of the epic are described in prose and analyzed. While analyzing the chapter of Hamd, the formation of special traditions (traditional introductory chapters: basmala, hamd, munojot, na't) in the history of Uzbek literature is also discussed. The article also assesses the poet's artistic skills